Minimum Quality Standards and Consumers Information - Paolo G. Garella; Emmanuel Petra (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
The literature so far has analyzed the effects of Minimum Quality Standards in oligopoly, using models of pure vertical differentiation, with only two firms, and perfect information. We analyze products that are differentiated horizontally and vertically, with imperfect consumers information, and more than two firms. We show that a MQS changes the consumers' perception of produced qualities. This increases the firms' returns from quality enhancing investments, notwithstanding contrary strategic effects. As a consequence, MQS policies may be desirable as both, firms and consumers, can gain. This contrasts with previous results in the literature and provides a justification for the use of MQS to improve social welfare.
Keywords: 330; Produktqualität; Oligopol; Asymmetrische Information; Produktdifferenzierung; Theorie